Portfolio Choice and Transactions Taxes - Markus Haberer (University of Konstanz, Center of Finance and Econometrics (CoFE), 2003)
In a simple portfolio choice model of two assets a foreign exchange transactions tax is implemented. We show that the graph in the mu-sigma[square] range is still a parabola and delineate its characteristics for altering tax rates. We presumed a risk avers investor seeking to minimize investment risks by international diversification of two uncorrelated assets. The main finding is that setting up a portfolio under the new tax condition leads to a higher transaction volume on international financial markets. In contrast, the transactions tax has got a stabilizing character when adjusting the portfolio to increased foreign investment risks.
urn:nbn:de:bsz:352-opus-11167
Keywords: O23; H29; H39; O16; G11; G15; G18; 330; International Financial Markets; Portfolio Choice; Risk Diversification; Tobin Tax; Transactions Tax; Portfolio-Management; international; Tobinsteuer; Internationaler Finanzmarkt; Börsenumsatzsteuer; Theorie